2012
DOI: 10.1111/j.1471-0528.2012.03482.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of postpartum sterilisation with the titanium clip versus partial salpingectomy: a randomised controlled trial

Abstract: A multicentre trial was conducted to compare efficacy of postpartum sterilisation with clip and partial salpingectomy. Life‐table estimates of pregnancy probabilities were compared through 2 years of follow up. A significantly different risk of pregnancy between the clip and partial salpingectomy groups was observed. Nine pregnancies were observed in the clip group versus two in the partial salpingectomy group. Cumulative probability of pregnancy through 2 years was 0.017 with the clip and 0.004 [correction ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Application of Filshie clips for postpartum sterilization is reported; however, several studies have demonstrated that, compared with partial salpingectomy, the clips are significantly less effective. 18,19 Postpartum partial salpingectomy is the most effective method of sterilization, with a 10-year cumulative failure rate of 7.5 failures per 1000 procedures. 5 In developing countries, interval minilaparotomy with partial salpingectomy may be the most common approach because of limited resources for purchase and upkeep of laparoscopic equipment.…”
Section: Female Sterilization: Open Abdominal Methodsmentioning
confidence: 99%
“…Application of Filshie clips for postpartum sterilization is reported; however, several studies have demonstrated that, compared with partial salpingectomy, the clips are significantly less effective. 18,19 Postpartum partial salpingectomy is the most effective method of sterilization, with a 10-year cumulative failure rate of 7.5 failures per 1000 procedures. 5 In developing countries, interval minilaparotomy with partial salpingectomy may be the most common approach because of limited resources for purchase and upkeep of laparoscopic equipment.…”
Section: Female Sterilization: Open Abdominal Methodsmentioning
confidence: 99%
“…For postpartum sterilisation, either the Filshie® (Utah Medical Products, Inc., Utah, USA) clip or modified Pomeroy (partial salpingectomy) techniques can be used, with both effective in this setting . Salpingectomy offers a slight reduction in the overall failure rate; however, Filshie® clip application tends to be quicker to perform . Evidence suggests a possible tubal origin for some types of epithelial ovarian cancers, so this may form part of the discussion and method selection in women undergoing sterilisation in the postpartum period.…”
Section: Method‐specific Guidancementioning
confidence: 99%
“…1,7,8 The use of mechanical devices that externally compress and occlude the fallopian tube, such as titanium (Filshie) clips, is discouraged in the postpartum period due to concern for decreased efficacy compared with methods of partial salpingectomy. [9][10][11] Although not recommended for postpartum use, titanium clips along with other mechanically occlusive devices such as silicone rubber bands and spring clips are effectively used for interval surgical PC. Other techniques such as electrocoagulation, which desiccates and damages the oviduct, and partial or total salpingectomy, which removes part or all of the extrauterine fallopian tube, are also commonly used for interval surgical PC.…”
Section: Surgical Tubal Ligation and Occlusionmentioning
confidence: 99%